Ultra-short race-pace training (USRPT) in swimming: Current perspectives - Nugent, F.; Comyns, T.; Kearney, P.; Warrington, G. (Open Access Journal of Sports Medicine, 2019)
Abstract: The last decade has seen a dramatic rise in sports science research due to the ever-increasing professionalization of sport. As a result, many alternative training methodologies that challenge traditional training philosophies have emerged. In the sport of swimming, ultra-short race-pace training (USRPT) was recently proposed. The aim of this article was to provide current perspectives on USRPT in competitive swimming. A systematic review was conducted to determine the effects of USRPT on performance in competitive swimmers. Of the 1347 studies retrieved, 1332 were excluded. The full-texts of 15 studies were assessed for eligibility. However, all 15 studies were excluded as the intervention did not consist of USRPT. Consequently, there are concerns surrounding USRPT as it is not currently based on peer-reviewed published literature. In addition, the recommendations within USRPT to avoid resistance training, cross-training activities, training intensities less than race-pace velocity and part practice swimming drills are highly controversial and lack scientific evidence. There is evidence to suggest that USRPT is a derivative of high-intensity training (HIT) and there is peer-reviewed published literature available to support the effects of HIT on performance in competitive swimmers. Swimming coaches and sports scientists are advised to consider the applications of USRPT with caution. The authors suggest that USRPT is a training method, which may be incorporated within a holistic periodized training program that includes a variety of training methods and stimuli. Future research should involve a randomized controlled intervention of USRPT in competitive swimmers.